(untitled) (Contemporary Journal of Social Science Review, 2026)
This research paper evaluate how Pakistani political legislatures communicate and maintain environmental issues in a diplomatic arena of ‘United Nations Framework Convention on Climate Change ‘Conferences of the Parties’ (COP)’ from 2015 to 2024, concentrating on discursive intersections, environmental governance, and ideologies. Through an interdisciplinary framework of Eco-critical discourse analysis (ECDA) by Arren Stibbe, complemented by Critical Discourse Analysis by Fairclough, this research adopts an interpretive, qualitative methodology to navigate how lexical and linguistic strategies shape and reshape ecological understandings in political narratives. A purposive sampling from diplomatic speeches delivered by Pakistan at COP21 to COP 29 has been evaluated using ECDA categories like framing, metaphor, identity, evaluation, and salience, together with lexical features ‘vocabulary, modality, and nominalization’ using CDA by Fairclough. The findings of this research reveal that representatives of Pakistan consistently expose green issues as most urgent, ethically charged, and deeply rooted in global justice considerations. This study also highlights that political and diplomatic discourse functions as an authentic tool to shape green realities, enabling state representatives of Pakistan to transform environmental vulnerability in the political and discursive capital while advocating green issues and equitable contribution at the COPs platform. This study recommends that future studies might expand to incorporate comparative critical analysis with other countries from the same global context, employing critical methodologies, or examining media reporting or public discourses on the same issues to maintain more comprehensive and inclusive understanding about green issues.